AKT-AMPKα-mTOR-dependent HIF-1α Activation is a New Therapeutic Target for Cancer Treatment: A Novel Approach to Repositioning the Antidiabetic Drug Sitagliptin for the Management of Hepatocellular Carcinoma - Abd El-Fattah, Eslam E.; Saber, Sameh; Youssef, Mahmoud E.; Eissa, Hanan; El-Ahwany, Eman; Amin, Noha A.; Alqarni, Mohammed; Batiha, Gaber El-Saber; Obaidullah, Ahmad J.; Kaddah, Mohamed M.Y.; Ahmed Gaafar, Ahmed Gaafar; Mourad, Ahmed A.E.; et al. (Frontiers in Pharmacology, 2022)
HIF-1α is a key factor promoting the development of hepatocellular carcinoma (HCC). As well, AKT-AMPKα-mTOR signaling is a promising target for cancer therapy. Yet, the AKT-AMPKα-mTOR-dependent activation of HIF-1α has not been studied in livers with HCC. In addition, the mechanisms underlying the potential antineoplastic effects of sitagliptin (STGPT), an antidiabetic agent, have not yet been elucidated. For that purpose, the N-nitrosodiethylamine (NDEA)-induced HCC mouse model was used in the present study using a dose of 100 mg/kg/week, i.p., for eight weeks. NDEA-induced HCC mice received STGPT 20, 40, or 80 mg/kg starting on day 61 up to day 120. The present study revealed that STGPT inhibited HIF-1α activation via the interference with the AKT-AMPKα-mTOR axis and the interruption of IKKβ, P38α, and ERK1/2 signals as well. Accordingly, STGPT prolonged the survival, restored the histological features and improved liver function. Additionally, STGPT inhibited angiogenesis, as revealed by a significant downregulation in the VEGF and mRNA expression of CD309 with concomitant inhibition of tissue invasion was evident by an increased ratio of TIMP-1/MMP-2. STGPT exhibited apoptotic stimulatory effect as indicated upon calculating the BCL-2/Bax ratio and by the gene expression of p53. The decrease in AFP and liver index calculation, gene expression of Ki-67 confirmed the antiproliferative activity of STGPT. The anti-inflammatory potential was revealed by the decreased TNF-α level and the downregulation of MCP-1 gene expression. Moreover, an antifibrotic potential was supported by lower levels of TGF-β. These effects appear to be GLP1R-independent. The present study provides a potential basis for repurposing STGPT for the inhibition of HCC progression. Since STGPT is unlikely to cause hypoglycemia, it may be promising as monotherapy or adjuvant therapy to treat diabetic or even normoglycemic patients with HCC.